Aesthetic expressions as data in researching the lived-world of children with advanced cancer - Galvez, Barbara Lyn; Kongsuwan, Waraporn; Schoenhofer, Savina O.; Hatthakit, Urai (Belitung Raya Foundation, Indonesia, 2021)
Background: Understanding the true world of children needs a special method. Using aesthetic expressions through artworks with reflections assists nurse researchers in exploring children’s feelings, thoughts, and behaviors in relation to their health and well-being. Objective: This article focuses on the use of aesthetic expressions as innovative data sources in a study of the lived worlds of children experiencing advanced cancer. Method: The use of aesthetic expressions in Gadamerian hermeneutic phenomenology and aesthetics, by means of van Manen’s approach using draw and write, is examined as a suitable approach in a study of the lived worlds of children experiencing advanced cancer. Results: The aesthetic expressions through the Draw-and-Write method of data generation were well-suited to a hermeneutic phenomenological study involving the group of Filipino children living with advanced cancer. The children drew images and figures of themselves, their families, classmates, friends, and teachers in several places and events during the series of two days. The drawings showed their facial expressions, home, parents, hospital stay, school activities, extracurricular activities, and other daily activities. Conclusion: Aesthetic expression linked to art and connected to human experience drew the participants into different realms and expanded their perceptual capacities so that the fullness of the meaning of the experience was appreciated. The understanding of the experience through aesthetic expression provided sensitivity to and awareness of the variation of experience among children with advanced cancer. It is hoped that this paper can contribute to an understanding of aesthetic expressions as pathways to understanding and support health professionals as they embark on their goal of creating or restoring a comfortable relationship with children.